PENYELESAIAN SENGKETA SERTIPIKAT GANDA PADA PTUN - Sandy Sulistiono; Widyawati Boediningsih (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The diversity of Indonesia's resources from land and sea has been recognized by the world. With this diversity of resources, the country certainly needs a legal umbrella to provide protection so that the potential of these natural resources is maintained into the future. So in this case, the state is in the position of